Salary, Nutrition and Quality of Life in the Construction Site of Greek Sanctuaries in the Classical Age. A Note (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2023)
L’articolo esamina alcuni aspetti relativi alla retribuzione dei lavoratori nei cantieri pubblici ateniesi durante l'età classica. Esso prende in considerazione anche delle fonti epigrafiche attiche di età classica, relative all'alimentazione degli artigiani, in rapporto con dati desunti da documenti cretesi e delfici. Si mettono infine in luce dettagli inerenti il trattamento di operai e artigiani di condizione liberae schiavile nel quadro dei lavori edilizi. The article deals with some aspects related to the salary of workers in the Athenian building projects during the Classical Age. It also takes into consideration some Attic epigraphic sources dating to the Classical Age, relating to the diet of the artisans, comparing them with Cretan and Delphic inscriptions. Finally, some details relating to the treatment of free men and slaves, as ergatai, in the context of public works are discussed.
Keywords: public works; Akropolis; salary of ergatai; economic growth